Modelling and analysis of three phase inverter with LCL filter - Mohamed Jameel Habib Mohamed (2019)
Filters have been used in inverters since early ages to suppress the harmonics that occur in output waveforms. This project aims to study the effects of various filters on the inverter. The standard of output is very important as it must be of the highest quality. Effective elimination of the discrepancies ensures least interruptions in power engineering. By making use of passive devices, noise and distortion can be eliminated. Inductors and capacitors serve as the major components used in filters. Three types of filters will be used in this project to observe the output differences. No changes will be made to the resistive load. Modelling is done on the software and real-time. DQ modelling is done for simplifying calculations. Use of a closed loop feedback used to create the duty cycles necessary for the PWM signals. According to Transmission Code by Energy Market Authority of Singapore, the total harmonics distortions for the 400V and 230V must not be more than 5.0 percent. Thus, it is imperative that the experiment is conducted to analyse the filters used to reduce the harmonics.